Computational tool for the analysis of HIV mutations associated with susceptibility or resistance to drugs (2009)
This  paper  presents  the  development  and  implementation  of  the  system  that  serves  as  a  tool  for  the  study  and exploration  of Human  Immunodefciency Virus  (HIV)  from  computational  analysis  of  these mutations,  taking genetic information itself. The analysis is performed using the information contained in the HIV genetic sequence and comparing it to reference sequences. Descriptions of the algorithms for alignment, mutation identifcation and resistance analysis applied to the genetic sequence of the virus are presented.